Effectiveness of Individual Nutritional Guidance with Supervised Cardiac Rehabilitation after Acute Myocardial Infarction - Ueda, Masami; Kawamoto, Yoshimi; Honma, Tomoaki; Fujiwara, Takashi; Morita, Natsumi; Kobayashi, Taira (Nihon Kanshikkan Gakkaishi, 2021)
Objective: To evaluate the effectiveness of nutritional guidance with supervised cardiac rehabilitation after acute myocardial infarction (AMI). Method: The subjects were 102 patients (85 males, mean age 67±10 years) who underwent supervised cardiac rehabilitation after AMI between December 2015 and June 2019. Nutritional guidance was provided 1 and 3 months after discharge, and three individual dietary changes were recommended for each patient. At 3 months after discharge, the rate of implementation of the three recommendations was evaluated. High and low adherence was defined as rates of ≥67% (HA group) and <67% (LA group), respectively. Risk factors for diet adherence were examined in these groups. Result: Nutritional guidance was conducted for 85 patients (83%) at 1 month and for 63 patients (62%) at 3 months. The median implementation rates were 80% at 1 month and 79% at 3 months. Low adherence was found in 12 patients (19%). Patients living alone and drinking excessive alcohol were more frequently observed in the LA group than in the HA group (p=0.04, p=0.03). Body mass index (BMI) had a tendency to be higher at baseline in the LA group (24.6±3.5 vs. 22.9±2.9 kg/m², p = 0.07) and showed a tendency to increase in this group after 5 months (p=0.08). Conclusion: Individual Nutritional guidance with three recommendations may be effective for patients who underwent supervised cardiac rehabilitation. However, particular care may be recommended for patients living alone, drinking excessive alcohol, or with higher BMI.